Contribution des trois emplois de à la fin à la structuration du discours : le temporel, l’aspectuel, le « reformulatif » - Christiane Marque-Pucheu (Discours)
We can distinguish three functions of à la fin in the second parts of coordinated and juxtaposed phrases, P0, P1 in which P1 contains the adverbial à la fin. We first compare three uses of the adverbial on the basis of qualities (scope, type of sentence, position in the sentence): a temporal use (à la fin1), an aspectual use (à la fin2) and a pragmatic use (à la fin3) expressing an attitude on the part of the speaker who intervenes to put an end to a state of affairs. We then show how, in spite of these differences, the three uses contribute to structuring the discourse. À la fin1 introduces an external enumeration (implying opposition to au début); à la fin2 introduces an internal enumeration, the repetition of the process in P0 that results in another process in P1 which can be translated by the paraphrase finir par and the possibility of introducing a relation of consecutive subordination between P0 and P1 ; à la fin3 aims to act on the addressee so that he ends the speech or action (finissons-en) expressed or not in P0.